2007
DOI: 10.2308/accr.2007.82.3.731
|View full text |Cite
|
Sign up to set email alerts
|

Information Pursuit in Financial Statement Analysis: Effects of Choice, Effort, and Reconciliation

Abstract: Prior research provides evidence that information affects financial statement users' judgments less when that information is provided in a less accessible format (e.g., information disclosed in a footnote or less prominent financial statement rather than being recognized on the income statement [Maines and McDaniel 2000]). We provide evidence that, conditional on users performing the analysis necessary to transform the financial statements to appear as if disclosed information had been recognized, that informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 48 publications
1
28
0
1
Order By: Relevance
“…This is common in early papers related to the capitalisation of finance leases (e.g., Munter and Ratcliffe ; Wilkins and Zimmer ; Breton and Taffler ), and in more recent studies by Hales et al. () and Nelson and Taylor () referring to the capitalisation of operating leases. Nelson and Taylor () argue that when users constructively capitalise operating leases, their decisions are more affected by this information than if leases were recognised from the outset, partially due to the larger effort made when off‐balance information is under analysis.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 79%
“…This is common in early papers related to the capitalisation of finance leases (e.g., Munter and Ratcliffe ; Wilkins and Zimmer ; Breton and Taffler ), and in more recent studies by Hales et al. () and Nelson and Taylor () referring to the capitalisation of operating leases. Nelson and Taylor () argue that when users constructively capitalise operating leases, their decisions are more affected by this information than if leases were recognised from the outset, partially due to the larger effort made when off‐balance information is under analysis.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 79%
“…In their experiment, participants were required to capitalise the disclosed future payments of operating leases to evaluate their impact on the firm's solvency position. Drawing on psychological theories on the pursuit of information, Nelson and Tayler (2007) hypothesised that disclosed information would be useful to investors in their assessment of a firm's riskiness when they had to expend effort to convert the disclosed (disaggregated) information to an aggregated basis (i.e., similar to recognition format). They found that effort had a positive effect on the usefulness of disclosed information.…”
Section: S -Financial Accountingmentioning
confidence: 99%
“…They found that when gains and losses were partly recognised in the Statement of Comprehensive Income, and partly disclosed in the notes, analysts were unable to distinguish between riskiness of exposed and hedged firms. Nelson and Tayler (2007) examined the impact of effort on the use of disclosed information. In their experiment, participants were required to capitalise the disclosed future payments of operating leases to evaluate their impact on the firm's solvency position.…”
Section: S -Financial Accountingmentioning
confidence: 99%
“…Although their findings are obviously relevant to managerial judgment and decision making, only a few scholars address this issue and report mixed findings. Nelson and Tayler (2007) demonstrated that participants who created information by themselves weighted it more heavily, however, they did not find a choice effect. Therefore, it is not clear if the information pursuit bias can be generalised to managerial decision making.…”
Section: Introductionmentioning
confidence: 83%